Psychological Intervention Strategies According to the Clinical Conditions and the Biopsychosocial Variables of the Adolescent in the Dental Practice: Review of the Literature - Amaíz DDS, Alejandro J.; Flores MSc, Miguel A. (Odovtos - International Journal of Dental Sciences, 2018)
Epidemiologically, the teenagers make up a population subgroup with oral indicators that need attention in the field of public health. In addition, the majority of the dental faculties orient the dental education directed to the child and the adult, where the attention focused to the teen is usually deferred. Moreover, the ignorance in the biopsychosocial alterations and the clinical peculiarities inherent to adolescence, make the attention of these potentially complex patients. Therefore, the objective of this article is to carry out a review of the literature in order to offer the professional the tools or psychological resources (soft skills) for the approach of the adolescent population that attends the dental consultation. Currently, the "Odontohebiatría" describes the comprehensive and interdisciplinary care of adolescent oral health, with an emphasis on oral prevention and esthetics. In this way, modern dentistry demands an active participation of the professional, who must be familiar with the clinical conditions and the psychological variables that may affect the teenager; also, it is considered important the instruction and training in strategies of psychological intervention to offer an attention adapted to this age group.